STUDY OF THE OZONE REACTION OF BENZYL ACETATE AND ITS DERIVATIVES IN THE LIQUID PHASE - HALSTIAN, ANDRII; VASHKURAK, JURII; KOSENKO, OLGA (Technologies and Engineering, 2022)
Purpose. Investigation of the kinetic regularities of the oxidation reaction of benzyl acetate and its derivatives by ozone in the liquid phase to determine the effect of alcohol on the ozonation of methylbenzenes by the methyl group. Methodоlogy. A 20 ml glass vessel equipped with a magnetic stirrer was loaded sequentially with a calculated amount of toluene or benzyl acetate of sulfuric acid and 10 ml of acetic anhydride. After dissolution, the reaction components were loaded into a thermostatic glass column. The column was connected to a reflux condenser, the resulting solution was cooled to the required temperature and ozone-containing gas was passed through it. Oxidation was carried out to a given degree of substrate conversion. The process was controlled by gas-liquid chromatography. The ozone concentration in the gas phase was determined spectrophotometrically on an SF-46 spectrophotometer. The concentration of toluene and its derivatives in the solution was determined by gas-liquid chromatography on the chromatograph with a flame-ionization detector on the column with a length of 1 m and a diameter of 3.5 mm, filled with a carrier – INERTON-Super (0.16–0.2 mm), with a fixed phase “FFAP” applied to it in the amount of 5% of the mass of the carrier under the following conditions: evaporator temperature is between 503–533 K; carrier gas velocity (nitrogen) – 2.0 L•h-1; hydrogen velocity – 1.8 L•h-1; air velocity – 18 L•h-1. Thermostating was carried out in the temperature range of 363–448 K, the temperature rise was carried out by the program - 8оC/min. Findings. The kinetic parameters of the ozonation reaction of benzylacetate and its derivatives in the liquid phase were studied. The rate constants of ozone reaction with benzyl acetate at different temperatures and the influence of the structure of substituents on its reactivity were determined. It is shown that the presence of electron-acceptor substituents increases the selectivity of oxidation along the side chain to 54%, and electron-donor – to a decrease of up to 8%. The kinetics of the reaction of ozone with benzyl acetate at a temperature of 293 K is described by a second-order equation that assumes a non-chain oxidation mechanism. At elevated temperatures, the chain consumption of ozone becomes noticeable due to its reaction with the products of destruction of the aromatic ring. Originality. For the first time, the kinetics of the oxidation reaction of benzyl acetate and its substituted ozone in the liquid phase, which significantly affects the equilibrium concentration of alcohols in the oxidation of the corresponding methylbenzene. It was found that depending on the structure of acylated benzyl alcohol, the oxidation selectivity along the side chain is from 8 to 54%. The reaction rate constants are determined and the mechanism of ozonation of benzyl acetate is proposed, which will allow optimizing the parameters for the development of technological bases for the production of benzyl alcohol and its derivatives by ozonation of methylbenzenes in the liquid phase. Practical value. The results are the basis for the development of low-temperature method for the synthesis of benzyl alcohols used in the production of active pharmaceutical ingredients.